One-year follow-up of blood-retinal barrier and retinal thickness alterations in patients with type 2 diabetes mellitus and mild nonproliferative retinopathy - Lobo, CL (2010)
OBJECTIVE: To examine the 1-year alterations of the blood-retinal barrier and changes in retinal thickness occurring in the macular region in patients with type 2 diabetes mellitus and mild nonproliferative retinopathy. METHODS: We classified 12 eyes of 12 patients with type 2 diabetes mellitus and mild nonproliferative retinopathy by 7-field stereoscopic fundus photography, levels 20 and 35 of Wisconsin grading, and examined them 3 times, at 6-month intervals, by fluorescein angiography, retinal leakage analyzer (RLA) (modified confocal scanning laser ophthalmoscope), and retinal thickness analyzer. The maps of retinal leakage and retinal thickness were aligned and integrated into one image. Data from the group of individuals with diabetes were compared with those from a healthy control population (n = 14; mean age, 48 years; age range, 42-55 years) to establish reference maps for the RLA and the retinal thickness analyzer. RESULTS: Areas of abnormally increased fluorescein sodium leakage and increased thickness were detected in all eyes examined at baseline. The sites of increased fluorescein leakage reached values as high as 483% above normal, but in 10 of the total 36 examinations performed, fluorescein leakage returned to normal levels. A statistically significant correlation was found between changes in hemoglobin A(1c) values and variations in percentage of abnormal fluorescein leakage between the 6- and 12-month examinations (P<.001). When comparing the RLA-leaking sites among the 3 examinations, a good correlation was seen among the location of these sites of maximum leakage, but there was a clear fluctuation in the percentage of increases. A correlation was noted between the location of the RLA-leaking sites and the location of areas of increased retinal thickness in subsequent examinations, either 6 or 12 months later. Microaneurysms showed relatively little leakage and leaked progressively less in successive examinations. CONCLUSIONS: The dominant alteration in the retina of patients with type 2 diabetes mellitus and mild nonproliferative retinopathy is the presence of RLA-leaking sites, indicating spotty retinal vascular damage characterized by alteration of the blood-retinal barrier. This damage appears to be reversible and directly associated with variations in glycemic metabolic control. Retinal edema appears to develop mainly as a result of retinal vascular leakage.